A framework of e-learning challenges during covid-19 in higher education institutions of Pakistan - Keerio, Imran Khan; Shah, Asadullah; Ali Shah, Masoomi Hifazat; Muhamad Ibrahim, Najhan; Mohd Mohadis, Hazwani; Ahmed Qureshi, Imran (IIUM Press, 2023)
eLearning is a process of acquiring information with the help of computing devices. The eLearning facility will be available anytime, anywhere, when these computing devices are connected to a network. The real benefit of eLearning was observed during covid-19 when all education institutions suspended their physical classes as social distance was necessary due to the pandemic situation in the world. While having serval advantages of eLearning, the researchers observed several problems, not only in the covid-19 case but even before the pandemic for its adoption/acceptance. Some of the well-known issues faced by the students of higher education institutions enlightened from the literature review are Cost, System Quality, System Complexity, Infrastructure, Social influence, facilitating conditions, and student learning motivations. These problems are still researchable, especially in an underdevelopment country like Pakistan. In this study, a framework has been developed with the help of various models and theories used for Information system research, i.e. (TAM3, UTAUT, M&D, TRA, and IDT). Observing problems from the literature review, some constructs/variables (Perceived Cost, System Quality, Complexity, Social Influence, Facilitating Condition, student learning motivation, PEOU, PU, and BI). are selected to make hypotheses for the framework. The study aims to find the most critical factors affecting eLearning’s slow acceptance/adoption throughout the covid-19 in Pakistan.